Shared leadership and project success: The mediational role of individual- and team-related factors - Beata Bajcar; Jolanta Babiak; Agata Klaus-Rosińska; Joanna Iwko; Dorota Kuchta (PLoS ONE, 2026)
The existing research on the role of shared leadership in achieving project success is rudimentary but suggests that this role may be important. In this study, we examined the relationship between shared leadership and project success, considering four potential mediators: individual engagement, justice (understood as perceived fairness), team building, and teamwork. We conceptualized project success as a construct with four dimensions: project performance, stakeholder satisfaction, project outcomes, and the subjective evaluation of project success. Alternatively, we allow it to refer to any one of these dimensions separately at the discretion of the decision maker. Our study employed structural equation modelling, surveys of 320 team members in Poland, and established measurement tools for the model variables. Our findings revealed simple mediating effects of individual engagement, team building, and teamwork in the relationship between shared leadership and project success. Additionally, this relationship was serially mediated by chains of factors: individual engagement and team building; justice and team building; individual engagement and teamwork; and justice and teamwork. We identified several strategies for various definitions of project success, which ensure efficient project management when shared leadership is applied. We also discuss the implications of our findings for project management theory and practice.